Unbalanced magnetron sputtering system for producing corrosion resistance multilayer coatings (2012)
In this work, an unbalanced magnetron sputtering system which allows for the production of corrosion resistance multilayer coatings is described. The major advantage of this system is that it combines features such as a multi-cathode setup, temperature control, control over the rotation of the sample holder, and the ability to change samples without breaking the vacuum. The system was tested with the production of Cr/CrN nanometric multilayers on AISI stainless steel 304 and silicon (100) substrates and the evaluation of its corrosion resistance. X-ray diffraction (XRD) was used in order to assess the crystalline microstructure and scanning electron microscopy (SEM) was used to characterize multilayer formation. The XRD results show (111) and (200) orientations for CrN multilayer films and the SEM results clearly show the formation of a multilayer structure. Corrosion resistance was evaluated through electrochemical studies and the results show that the Cr/CrN multilayer structure presents lower corrosion current and higher corrosion potential as compared to the stainless steel 304 substrate.